DIFFERENTIAL EXPRESSION OF TOLL-LIKE RECEPTOR18 (TLR18) MRNA IN PANGASIUS PANGASIUS INDUCED WITH EDWARDSIELLA TARDA - JAWAHAR RAJ. K; UMA. A; REBECCA. G (International Journal of Pharma and Bio Sciences, 2012)
Toll-like receptors (TLRs) are a family of germline-encoded pattern-recognition receptors involved in recognizing diverse molecular patterns of the invading pathogens called pathogen associated molecular patterns (PAMPs). TLRs play an important role as regulators of innate and adaptive immune responses in fishes. TLRs specifically recognize the ligands and activate various cascades of pathways to destroy the pathogens. About 17 different TLR types (TLR 1, 2, 3, 4, 5, 5S, 7, 8, 9, 13, 14, 18, 19, 20, 21, 22, 23) have been identified in teleost fishes with specificity in identifying the ligands. Studies on the expression profiles of TLR18 in teleost fishes are scanty. Hence, this study was carried out with an objective to assess the expression profile of TLR18 in Pangasius pangasius (a freshwater cat fish species) by inducing with Edwardsiella tarda, a gram-negative bacterial pathogen infecting fish. Real-time quantitative PCR analysis was performed to study the differential expression of TLR18 in skin, gill, , liver, intestine, kidney and spleen tissue of P.pangasius. The results of real-time quantitative PCR analysis showed differential and induced expression of TLR18 in various tissues of P.pangasius at various time intervals, 2h, 6h, 24h and 48h post exposure with E.tarda.